Can host density attenuate parasitism?. (16th August 2016) - Magalhães, L.; Freitas, R.; Dairain, A.; De Montaudouin, X.
Abstract : Bivalve populations display fluctuating densities resulting in different interactions among them and with their environment. Using the edible cockle ( Cerastoderma edule ) as a model, we investigated two alternative hypotheses concerning the effect of density on individual infection intensity by trematode parasites. Considering that these parasites infect cockles through filtration activity, our first hypothesis was that high host density will have a dilution effect so that infection intensity decreases with host density. Conversely, high cockle density could attract other hosts used by these trematode parasites to complete their life cycle. A 17-year monthly survey of a cockle population in Arcachon Bay, France, showed a negative correlation between the cockle density and the abundance of parasite larvae in juvenile cockles with a significant threshold when adult cockle density reached 400 ind. m −2 . This result was confirmed for the four dominating trematode parasites, independently considered. Additionally, a field experiment was performed during 9 months, with cockles maintained in enclosures with two densities (200 and 800 ind. m −2 ). Individual cockle mean infection was 1.5 times higher at low cockle density, mainly due to one dominant trematode species ( Parvatrema minutum ). In conclusion and confirming the first advanced hypothesis, for certain environments, negative consequences of bivalve intraspecific competition at high density can be mitigated by lower parasite pressure.